Size-controlled Chevrel Mo6S8 as Cathode Material for Mg Rechargeable Battery - Anna Ryu; 박민식; Woosuk Cho; 김점수; 김영준 (Bulletin of the Korean Chemical Society, 2013)
Nanoscale Chevrel Mo6S8 powders are synthesized by molten salt synthesis. Synthesized Mo6S8 powders have different mean particle sizes which are dependent on a ratio of salt to precursor. The particle sizes of Mo6S8 powders changes along with the ratio increase. Mo6S8 (6:1) demonstrates the best electrochemical characteristics among the synthesized Mo6S8 powders although the Mo6S8 (4:1) has the smallest particle size. Mo6S8 (6:1) shows a reversible capacity of 83.9 mAhg−1, which is 27.5% and 33% improved value over Mo6S8 (2:1) and Mo6S8 (4:1) at a current density of 0.2C, respectively. The superior electrochemical properties of Mo6S8 (6:1) are attributed to the balanced particle size which provides proper contact area with electrolyte and the shortened Mg2+ diffusion length. The Mo6S8 (4:1) has the smallest particle size but further reduction of particle size from Mo6S8 (6:1) is not advantageous. KCI Citation Count: 11